Placement of inertial measurement units in Racket Sports: Perceptions of coaches for IMU use during training and competition - Wylde, M. J.; Masismadi, N. A.; Yong, L. C.; Callaway, A. J.; Williams, J. M. (International Journal of Racket Sports Science, 2021)
While inertial measurement units (IMU) have become an integral part of sports performance analysis, upper body-mounted IMUs have been found to exhibit poor reliability in measuring lower-limb loading. In racket sports, IMUs have been placed in a number of positions on the upper body, lower body and racket in a research setting. A potential limitation to the concurrent use of multiple IMUs is that coaches may be reluctant to allow their athletes to wear the units during training and competition due to concerns that the units would interfere with athlete movement. This study seeks to understand the perceptions of racket sports coaches towards the use of IMUs in training and competition. A total of 58 racket sport coaches responded to a survey on the use of IMUs during training and competition. Based on the responses, 96.6% (56 out of 58) of coaches indicated that they would allow their athletes to wear IMUs in training, while 65.5% (38 out of 58) would allow their athletes to wear IMUs during competition. For use in training, 9 of the 14 suggested IMU placements received significant positive responses. However, none of the suggested IMU placements received significant positive responses for use during competition and 11 of the 14 received significant negative responses. This suggests that coaches understand the benefits of collecting data from IMUs during competition there remains concern regarding inconvenience to the athlete, lack of comfort, and appearance. Despite this, for use in training, a number of upper and lower body- mounted IMUs placements have the potential to be part of regular monitoring in racket sports.